Peptidomimetic inhibitor of L-plastin reduces osteoclastic bone resorption in aging female mice - Aljohani, Hanan (Bone Res, 2021)
L-plastin (LPL) was identified as a potential regulator of the actin-bundling process involved in forming nascent sealing zones (NSZs), which are precursor zones for mature sealing zones. TAT-fused cell-penetrating small molecular weight LPL peptide (TAT- MARGSVSDEE, denoted as an inhibitory LPL peptide) attenuated the formation of NSZs and impaired bone resorption in vitro in osteoclasts. Also, the genetic deletion of LPL in mice demonstrated decreased eroded perimeters and increased trabecular bone density. In the present study, we hypothesized that targeting LPL with the inhibitory LPL peptide in vivo could reduce osteoclast function and increase bone density in a mice model of low bone mass. We injected aging C57BL/6 female mice (36 weeks old) subcutaneously with the inhibitory and scrambled peptides of LPL for 14 weeks. Micro-CT and histomorphometry analyses demonstrated an increase in trabecular bone density of femoral and tibial bones with no change in cortical thickness in mice injected with the inhibitory LPL peptide. A reduction in the serum levels of CTX-1 peptide suggests that the increase in bone density is associated with a decrease in osteoclast function. No changes in bone formation rate and mineral apposition rate, and the serum levels of P1NP indicate that the inhibitory LPL peptide does not affect osteoblast function. Our study shows that the inhibitory LPL peptide can block osteoclast function without impairing the function of osteoblasts. LPL peptide could be developed as a prospective therapeutic agent to treat osteoporosis.